ANALYSIS OF PRODUCTION CAPACITY OF NOBU PINK CERAMIC TYPE USING CAPACITY REQUIREMENT PLANNING METHOD AT PT ARWANA CITRAMULIA TBK PLANT I - Ponda, Henri; Fatma, Nur Fadilah; Rahmawaty, Anggie Fitri (Heuristic, 2024)
PT. Arwana Citramulia Tbk is a manufacturing company that produces ceramics. The company faces challenges in managing fluctuating demand, making it difficult to effectively plan production capacity. The objective of this research is to determine the ideal production capacity for the Nobu Pink ceramic type. The analysis of the production capacity for Nobu Pink ceramics was conducted at PT. Arwana Citramulia Tbk Plant I using the Capacity Requirement Planning (CRP) method, with capacity calculations performed using the bill of labor (BOL) method. The research results indicate that the production capacity for 25 x 25 cm Nobu Pink ceramics is 633 pieces per hour or 15,192 pieces per day. A comparison of available capacity with required capacity shows a shortage of capacity at the Kiln workstation in each period. A proposed solution for the company is to add 3 hours of overtime work on Saturdays, which would meet the capacity shortage.